Breast cancer screening knowledge and practices among nursing students in Kuala Terengganu - Husbani, Mohd Amin Rebuan; Myat Moe, Thwe Aung; Nurulhuda, Mat Hassan; Hamidah, Othman (2017)
In Malaysia, females suffering from breast cancer often present late when their cancer has progressed to advanced stages. Lack of knowledge among population is one of the the factor that act as a barrier to prevent the patient to come early. Nursing staffs are one of the front-liner person in medical services and thus they are the referring person for the public to seek the information. To assess the awareness and practice of the breast cancer screening among nursing students.This is a cross sectional study involving 89 nursing students from School of Nursing Science, Medical Faculty, University Sultan Zainal Abidin (UniSZA) done from 1st of March till 15th of March 2016. A self-administered questionnaire was given intended to provoke their sociodemographic information and knowledge of the breast cancer screening and their practices towards breast cancer screening. Data analysis was carried out using SPSS Version 21.Eighty-nine participants fully responded. Overall the students‟ knowledge regarding symptoms of breast cancer was good with majority knowing the common symptoms and screening methods of breast cancer with 87 (97.8%), 83 (93.3%) and 85 (95.5%) respondents know about breast self-examination, clinical breast examination and mammogram respectively. Students‟ had variable knowledge on risk factor (family history, 49.4%, contralateral cancer, 55.1%, increasing age, 83.1%) for having breast cancer. Only 41 students (46.1%) carried out the breast self-examination procedure and 5 participants (5.6%) had clinical breast examination.The overall students had good knowledge about the common symptoms of breast cancer and its screening programmes however lack of practice among them. More programme must be done to increase the awareness of the breast cancer screening programme among nursing students thus they will be able to transfer the knowledge to the public effectively.